The component analysis of liquid smoke from rice hulls and its toxicity test on baby hamster kidney cells - Ira Arundina; Indeswati Diyatri; Meircurius Dwi Condro Surboyo (GarVal Editorial Ltda., 2021)
Context: The pyrolysis product of rice hulls (Oryza sativa) has been used for the natural preservation of food and shows the potential to act as an antioxidant and anti-inflammatory product. However, the safety of this treatment has still not been studied. Aims: To analyse liquid smoke derived from rice hulls (Oryza sativa) components, its physical characteristics including acidity, density, and its toxicity on baby hamster kidney (BHK) cells. Methods: The physical characteristics of acidity and density were analysed using a digital pH meter and gravimetry. The components of liquid smoke from rice hulls were analysed using gas chromatograph mass spectrometry. Eight concentrations (1, 2.5, 5, 7.5, 10, 12.5, 15 and 17.5%) of liquid smoke from rice hulls were used and immersed in media culture for 24 hours. Then, the MTT assay method was used to investigate the cytotoxic effect on BHK cells. Optic formazan density was indicated from the number of living cells. Results: The acidity of liquid smoke from rice hulls was 2.296 and the density is 1.0102 g/mL. The components analysed were 2-methoxyphenol (13.45%), mequinol (13.45%) and phenol (10.52%). The 10% concentration showed the highest number of living cells at 49.33%, while liquid smoke rice hulls had 12.5% of cells still alive (p=0.000), followed by the concentration of 7.5% (p=0.000), concentration of 5% (p=0.000) and liquid smoke rice hulls at 1% (p=0.000). Conclusions: Liquid smoke from rice hulls (Oryza sativa) showed that it's potential of toxicity may be related its high acidity, components and the concentration.